2019
DOI: 10.1371/journal.pone.0218736
|View full text |Cite
|
Sign up to set email alerts
|

LL-37 alone and in combination with IL17A enhances proinflammatory cytokine expression in parallel with hyaluronan metabolism in human synovial sarcoma cell line SW982—A step toward understanding the development of inflammatory arthritis

Abstract: LL-37 is the only human cathelicidin-family host defense peptide and has been reported to interact with invading pathogens causing inflammation at various body sites. Recent studies showed high levels of LL-37 in the synovial-lining membrane of patients with rheumatoid arthritis, a common type of inflammatory arthritis. The present study aims to investigate the role of LL-37 on mechanisms associated with pathogenesis of inflammatory arthritis. The effects of LL-37 on the expression of proinflammatory cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…SS typically occurs in young adults and has a poor prognosis, with a tendency to relapse and metastasize at a late stage. [ 3 ] Currently, surgery is the only option for comprehensive treatment. Radiotherapy, chemotherapy, and targeted molecular therapy are considered as additional options following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…SS typically occurs in young adults and has a poor prognosis, with a tendency to relapse and metastasize at a late stage. [ 3 ] Currently, surgery is the only option for comprehensive treatment. Radiotherapy, chemotherapy, and targeted molecular therapy are considered as additional options following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, LL-37 also induces IL-17A expression. Moreover, long activation of IL-17A by LL-37 and cooperation of these two mediators, prolong and enhance the main inflammatory processes in tissues [42]. Overall, the synergy of LL-37 and IL-17A, HBD-3 and HBD-4 supports the hypothesis that synergistic cooperation of different immune factors can lead to a higher response to pathogens and faster reduction of inflammation.…”
Section: Introductionmentioning
confidence: 55%
“…Further in vitro studies had found that CAMP gene methylation inhibited the level of ROS and TNF-α in chondrocytes, promoted the level of TGF-β expression, inhibited the proliferation of chondrocytes, and promoted their apoptosis. The results of Kuensaen et al [36] found that high levels of CAMP promote the expression of downstream pro-in ammatory cytokines (especially IL17A), which was related to the pathogenesis of in ammatory arthritis. Hu et al [37] found that CAMP regulated the production of in ammatory cytokines such as TNF-α and inhibited cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%